Remembrance, History, and Justice : Coming to Terms with Traumatic Pasts in Democratic Societies - Tismăneanu, Vladimir; Iacob, Bogdan C. (2015)
The twentieth century has left behind a painful and complicated legacy of massive trauma, monstrous crimes, radical social engineering creating collective/individual guilt syndromes that were often specters haunting the process of democratization in the various societies that have emerged out of these profoundly de-structuring contexts, such as Germany, Romania, Russia, and others. The volume is an up-to-date reassessment of how the interplay between memory, history, and justice gives the reader insights that examine the present and future of democracy without becoming limited to a Europe-centric framework of understanding. The analysis is structured on three complementary and interconnected trajectories: the public use of history, politics of memory, and transitional justice